Increasing the spatial resolution and sensitivity of magnetic resonance elastography by correcting for subject motion and susceptibility-induced image distortions - Fehlner, Andreas; Hirsch, Sebastian; Weygandt, Martin; Christophel, Thomas; Barnhill, Eric; Kadobianskyi, Mykola; Braun, Juergen; Bernarding, Johannes; Luetzkendorf, Ralf; Sack, Ingolf; Hetzer, Stefan (Journal of Magnetic Resonance Imaging, 2017)
Purpose: To improve the resolution of elasticity maps by adapting motion and distortion correction methods for phase-based magnetic resonance imaging (MRI) contrasts such as magnetic resonance elastography (MRE), a technique for measuring mechanical tissue properties in vivo. Materials and Methods: MRE data of the brain were acquired with echo-planar imaging (EPI) at 3T (n = 14) and 7T (n = 18). Motion and distortion correction parameters were estimated using the magnitude images. The real and imaginary part of the complex MRE data were corrected separately and recombined. The width of the point-spread function (PSF) and the position variability were calculated. The images were normalized to the Montreal Neurological Institute (MNI) anatomical template. The gray-to-white matter separability of the elasticity maps was tested. Results: Motion correction sharpened the |G*| maps as demonstrated by a narrowing of the PSF by 0.78 ± 0.51 mm at 7T and 0.52 ± 0.63 mm at 3T. The amount of individual head motion during MRE acquisition correlated with the decrease in the width of the PSF at 7T (r = 0.53, P = 0.025) and at 3T (r = 0.69, P = 0.006) and with the increase of gray-to-white matter separability after motion correction at 7T (r = 0.64, P = 0.0039) and at 3T (r = 0.57, P = 0.0319). Improved spatial accuracy after distortion correction results in a significant increase in separability of gray and white matter stiffness (P = 0.0067), especially in inferior parts of the brain suffering from strong B0 inhomogeneities. Conclusion: We demonstrate that our method leads to sharper images and higher spatial accuracy, raising the prospect of the investigation of smaller brain areas with increased sensitivity in studies using MRE. Level of Evidence: 1. Technical Efficacy: Stage 1. J. MAGN. RESON. IMAGING 2017;46:134–141.
CRIS-Team Scopus Importer:2022-08-03
Keywords: distortion correction; motion correction; MR elastography; multifrequency MRE; phase-based contrast